Reading for Normal: Young People and YA Fiction in the Time of Covid‑19 - Waller, Alison; Dashwood, Rita (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
The Reading for Normal project discussed in this article sought to interrogate some of the assumptions about “normality” that underpin everyday life, and to understand how reading fictional representations of ordinary life might help young readers better manage periods of uncertainty and instability. Using data from a small‑scale UK‑based reading group project that ran from December 2020 to May 2021, we explore the affordances of authenticity, belonging, and connection that emerged when teens were offered opportunities for a “common dwelling in fictional ordinariness with a generational cohort”. We consider the ways in which reading and talking about young adult (YA) fiction helps teenage readers address questions about the changing world around them.